1967
DOI: 10.46429/jaupr.v51i1.11218
|View full text |Cite
|
Sign up to set email alerts
|

Título en español.

Abstract: Immature sugarcane was treated with chemical additives to determine whether significant and predictable changes could be induced in enzyme behavior. All plants were grown in sand culture with controlled nutrient supply. One group received foliar application of ascorbic acid, cysteine, hydroxylamine and cyanide; the other group received silicon, iron, and cyanide as nutrient-solution supplements. Enzymes assayed included acid phosphatases, invertase, amylase, peroxidase, and tyrosinase (polyphenoloxidase). Each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…6). This is because Si induces sugar production in the leaves and transports it to the sugarcane stems [16][17][18].The enzymatic action of Si in the stem delays the inverse reactions and the terminal oxidation of sugars, increasing sucrose production and decreasing reducing sugars [17]. Added to this is the fact that Si deposited on the cell wall can regulate the transport of soluble sugars via physiological or physical mechanisms not described by the authors [43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6). This is because Si induces sugar production in the leaves and transports it to the sugarcane stems [16][17][18].The enzymatic action of Si in the stem delays the inverse reactions and the terminal oxidation of sugars, increasing sucrose production and decreasing reducing sugars [17]. Added to this is the fact that Si deposited on the cell wall can regulate the transport of soluble sugars via physiological or physical mechanisms not described by the authors [43].…”
Section: Discussionmentioning
confidence: 99%
“…With respect to the sugarcane crop, both high stem production and quality are needed, and the amount of sugar produced, and potential sugarcane sugar recovery are attributes that determine the economic yield of the crop. Classic studies reported a direct relation between Si supply and sugarcane sugar production [16][17][18], but this has yet to be con rmed.…”
Section: Introductionmentioning
confidence: 99%